The effect of self-determination skills training on academic vitality and optimism in students with hearing loss: a quasi-experimental study - Tabatabii , Zahra; Norouzi, Ghasem; Abedi , Ahmad (Social Determinants of Health, 2022)
Background: Hearing impairment, even if mild, can delay linguistic development and negatively affect the language acquisition process. This study designed to investigate the effect of self-determination skills training on academic vitality and optimism in students with hearing loss. Method: This was a quasi-experimental study with pretest-posttest design and control group. The sample consisted of 30 students with hearing loss in Shahroud who were selected by available sampling method and randomly and equally assigned to the experimental and control groups (15 people in each group). The experimental group participated in a self-determination skills training program that was conducted in 8 sessions of 40 minutes (one session per week), while the control group did not participate in this program. Participants were assessed using the Academic Vitality Questionnaire and Optimism Questionnaire. Data were analyzed using univariate and multivariate analysis of covariance tests and SPSS-23 software Results: Considering the differential results of multivariate analysis of covariance for experimental and control groups in the variables of academic vitality (P = 0.001) and academic optimism (P = 0.001), the difference between the experimental and control groups is significant. According to Eta squared, it can be said that in the variables of academic vitality and academic optimism, 33% and 39% of these changes are due to intervention, respectively. Conclusion: This study emphasizes the role of self-determination interventions in positive academic variables. This method can be used in the educational and rehabilitation program of this group of children.